Characteristics and outcomes of young patients with ST segment elevation myocardial infarction undergoing primary percutaneous coronary intervention: retrospective analysis in a multiethnic Asian population. Issue 1 (13th January 2021) - Tung, Benjamin WL; Ng, Zhe Yan; Kristanto, William; Saw, Kalyar Win; Chan, Siew-Pang; Sia, Winnie; Chan, Koo Hui; Chan, Mark; Kong, William; Lee, Ronald; Loh, Joshua P; Low, Adrian F; et al.
Abstract : Objective: ST segment elevation myocardial infarction (STEMI) is associated with significant mortality leading to loss of productive life years, especially in younger patients. This study aims to compare the characteristics and outcomes of young versus older patients with STEMI undergoing primary percutaneous coronary intervention (PPCI) to help focus public health efforts in STEMI prevention. Methods: Data from the Coronary Care Unit database of the National University Hospital, Singapore from July 2015 to June 2019 were reviewed. Patients were divided into young (<50 years old) or older (≥50 years old) groups. Results: Of the 1818 consecutive patients with STEMI who underwent PPCI, 465 (25.6%) were <50 years old. Young compared with older patients were more likely to be male, current smokers, of Indian ethnicity, have family history of ischaemic heart disease (IHD) and had lower 1 year mortality (3.4% vs 10.4%, p<0.0001). Although diabetes, hypertension or dyslipidaemia was less common among young patients, the prevalence of having any one of these risk factors was high in the range of 28% to 38%. Age was an independent predictor of mortality in the older but not younger patients with STEMI, and diabetes showed a trend towards mortality in both groups. Conclusion: Young patients with STEMI are more often smokers, of Indian ethnicity and had family history of IHD, although cardiometabolic risk factors are also prevalent. Mortality is lower, but not negligible, among the young patients with STEMI. Public health efforts are needed to reduce the prevalence of these risk factors among the constitutionally susceptible population.